Are China's Farms Growing?. (18th January 2016) - Ji, Xianqing; Rozelle, Scott; Huang, Jikun; Zhang, Linxiu; Zhang, Tonglong
Abstract: China's agricultural sector faces challenges because most farms are still small scale. China's policy is to encourage the consolidation of farms and promote farms that are larger in scale. A question that arises is: Are China's farms growing? The goal of the present paper is to determine whether large farms in China have emerged or if farms remain small. To meet this goal, we systematically document the trends in the operational sizes of China's farms and measure the determinants of changes in farm size. Using a nationally representative dataset, the study shows that in 2013 China's farming sector was still mostly characterized by small‐scale farms. However, at the same time, there is an emerging class of middle‐sized and larger‐sized farms. Most large farms are being run by households but there is a set of large farms that are company/cooperative‐run. Today, farmers on larger farms are younger and better educated than the average farmer.